An experimental investigation into queueing behavior - Anna Conte; Marco Scarsini; Oktay Sürücü (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We conduct an experiment meant to explore the factors driving customers' decisions in a queueing system. Under different time allowance conditions, the experimental subjects are asked to join one of two queues that differ in their length, server speed, and entry fee. We investigate some aspects of a queue on which subjects base their decision and what is the effect of time pressure on their decision criteria. We find that only a proportion of subjects behave rationally and use the relevant information efficiently. The size of this proportion increases when time limitation is relaxed. The rest of the subjects seem to adopt a rule of thumb that ignores the information on server speed and follows the shorter queue. Consequently, these subjects use less time than rational types when making their decisions. Furthermore, time pressure harms decision performance since the presence of time limitation stresses a great deal of subjects and causes them to use time inefficiently.
Keywords: C91; L00; C33; C35; 330; decision times; join the shortest queue; laboratory experiments; queues with entry fee